2014
DOI: 10.14778/2732977.2732988
|View full text |Cite
|
Sign up to set email alerts
|

Similarity search for scientific workflows

Abstract: With the increasing popularity of scientific workflows, public repositories are gaining importance as a means to share, find, and reuse such workflows. As the sizes of these repositories grow, methods to compare the scientific workflows stored in them become a necessity, for instance, to allow duplicate detection or similarity search. Scientific workflows are complex objects, and their comparison entails a number of distinct steps from comparing atomic elements to comparison of the workflows as a whole. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 36 publications
(102 reference statements)
1
64
0
Order By: Relevance
“…However, these comparisons were performed on very small and welldocumented workflow sets, and thus the results should not be extrapolated to the large, but shallowly annotated repositories that exist today. To verify this hypothesis, in prior work we performed a large-scale comparative evaluation of workflow similarity search algorithms [14]. Our results indicated that a) structure-based methods are indispensable for some current repositories which lack rich annotations, b) structure-based methods, once properly configured, outperform annotationbased methods even when such rich annotations are available, and c) any such standalone approach is further beaten by ensembles of annotation-based and structure-based methods.…”
Section: Introductionmentioning
confidence: 82%
“…However, these comparisons were performed on very small and welldocumented workflow sets, and thus the results should not be extrapolated to the large, but shallowly annotated repositories that exist today. To verify this hypothesis, in prior work we performed a large-scale comparative evaluation of workflow similarity search algorithms [14]. Our results indicated that a) structure-based methods are indispensable for some current repositories which lack rich annotations, b) structure-based methods, once properly configured, outperform annotationbased methods even when such rich annotations are available, and c) any such standalone approach is further beaten by ensembles of annotation-based and structure-based methods.…”
Section: Introductionmentioning
confidence: 82%
“…Some workflow similarity measurements are text based [19], and some others consider different aspects of workflows (such as workflow motifs [17], or workflow structures [1,20]). For example a workflow similarity measurement method is the work at [19] that used feature selection techniques based on text.…”
Section: Related Workmentioning
confidence: 99%
“…The tool used was Protégé 4.x 1 . Protégé is mainly used for ontology demonstration but it also provides some features to workflow demonstration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the clustering is done on the entire workflows without considering the sub-clustering of individual workflow tasks. In spite of some other works similar the work of [22]. In the work of [22] normalization with regard to sizes of compared workflows is done as a post processing step.…”
Section: Introductionmentioning
confidence: 99%